2022
DOI: 10.1097/mcc.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Subphenotypes of acute kidney injury in children

Abstract: Purpose of reviewThe purpose of this review is to describe acute kidney injury (AKI) phenotypes in children.Recent findingsAKI is a heterogenous disease that imposes significant morbidity and mortality on critically ill and noncritically ill patients across the age spectrum. As our understanding of AKI and its association with outcomes has improved, it is becoming increasingly apparent that there are distinct AKI subphenotypes that vary by cause or associated conditions. We have also learned that severity, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…With the development of biomarker-guided risk assessment [47], the nomenclature of kidney failure has broadened, and the use of tubular markers enables earlier recognition of AKI, which is important not only for optimizing treatment, but also for preventing chronic complications. This is complemented by the alert systems-one of the best-known of which is the RAI (renal angina index) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of biomarker-guided risk assessment [47], the nomenclature of kidney failure has broadened, and the use of tubular markers enables earlier recognition of AKI, which is important not only for optimizing treatment, but also for preventing chronic complications. This is complemented by the alert systems-one of the best-known of which is the RAI (renal angina index) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a multicenter pilot study of 98 infants undergoing cardiac surgery found that uKIM-1 at 6 hours was associated with CS-AKI ( 34 ). The inconsistent association between urine biomarker concentrations and CS-AKI in infants is likely multifactorial but may be due to heterogeneous mechanisms of injury in CS-AKI or limitations of current CS-AKI definitions that fail to account for age- and disease-related renal changes in this population ( 35 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…CS-AKI represents a heterogeneous disease process that both contributes to and is a consequence of FO ( 35 ). Capillary leak after bypass results in generalized fluid retention, which increases renal subcapsular pressure resulting in renal injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations